THE RELATION BETWEEN AUTHENTIC LEADERSHIP, BUSINESS CAPABILITIES AND BUSINESS PERFORMANCE - Zehir, Cemal; Hemedan, Isa; Sehitoglu, Yasin; Erzengin, Esra (FUTURE ACAD, 2019)
The study examines the relation between authentic leadership, business capabilities such as learning, entrepreneurship, product development and business performance. The study comprises of a qualitative research which includes a comprehensive literature review. Leadership style, particularly authentic leadership which has a significant effect on business capabilities (learning, entrepreneurship, product development) is explained in detail. According to the hypotheses of the study; it is put forward that authentic leadership effects capabilities of a company such as learning, entrepreneurial and product development. On the other hand, learning, entrepreneurial and new product development capabilities effect business performance. According to the literature review conducted within the study, it is observed that authentic leadership effects a company's learning, entrepreneurial and product development capabilities positively as well as learning, entrepreneurial and new product development capabilities effect business performance in a positive way. Further studies including quantitative research is recommended since the study consists of a qualitative research. (C) 2019 Published by Future Academy www.FutureAcademy.org.UK
Keywords: Authentic leadership; learning capability; entrepreneurship capability; product development capability; RESOURCE-BASED VIEW; ENTREPRENEURIAL ORIENTATION; PRODUCT DEVELOPMENT; LEARNING ORIENTATION; FIRM PERFORMANCE; COMPETENCE; Business & Economics